2003
DOI: 10.2337/diacare.26.3.750
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Web-Based Diabetes Disease Management

Abstract: OBJECTIVE -To test effects of a web-based decision support tool, the diabetes Disease Management Application (DMA), developed to improve evidence-based management of type 2 diabetes.RESEARCH DESIGN AND METHODS -We conducted a group randomized controlled trial of 12 intervention and 14 control staff providers and 307 intervention and 291 control patients with type 2 diabetes in a hospital-based internal medicine clinic. Providers were randomly assigned from May 1998 through April 1999 to have access to the DMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 32 publications
3
164
3
Order By: Relevance
“…Our results present a less optimistic picture of the potential benefits of web platforms for the empowerment of patients with chronic diseases than some of the previous literature (Harno et al, 2006;Meigs et al, 2003;and McKay et al, 2001).…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…Our results present a less optimistic picture of the potential benefits of web platforms for the empowerment of patients with chronic diseases than some of the previous literature (Harno et al, 2006;Meigs et al, 2003;and McKay et al, 2001).…”
Section: Resultscontrasting
confidence: 44%
“…They found significantly lower levels of HbA1c, blood pressure, cholesterol and fasting plasma glucose in the study group relative to the control individuals, and a lower number of visits by the study patients to doctors and nurses. Meigs et al (2003) tested the effects of the Disease Management Application (DMA), a web-based decision support tool for diabetics developed to improve evidence-based management of type 2 diabetes.…”
Section: Background and Significancementioning
confidence: 99%
“…There is substantial evidence to support this third point as well. [32][33][34][35][36][37][38] While the clinical points made by Phillips disease care. In chronic disease management, the task faced by health care providers (and the patient) is one in which decisions are made to control a process that is manifest in varying states of patient health.…”
Section: Physician Factors That Contribute To Clinical Inertiamentioning
confidence: 99%
“…Three recent randomized trials illustrate both the potential and the limitations of currently available decision support systems for chronic disease care. 35,36,60 In 2003, Meigs et al 36 reported that an electronic medical record (EMR) that prompted physicians to intensify therapy, but did not provide tailored or specific decision support (what drug, what dose), failed to improve A1c levels. In a 2002 Mayo Clinic study, a similar rudimentary decision support delivered through an EMR system increased frequency of A1c testing but failed to improve A1c levels.…”
Section: Enhanced Primary Care-clinical Decision Supportmentioning
confidence: 99%
“…Although some uncontrolled studies have reported benefits regarding metabolic control, 7,8 recent controlled studies have demonstrated little or no such benefits besides the EMRs helping to increase the number of tests ordered. 9,10 Other newer e-health strategies that have been evaluated in diabetes management include the Internet combined with short message service (SMS), 11 Web-based support systems, 12,13 electronic clinical reminders incorporated into diThis article was externally peer reviewed. Submitted 20 September 2006; revised 15 Decemberabetes self-care education programs, 14,15 and the PDA.…”
mentioning
confidence: 99%